Development of Emulgel Delivery of Mupirocin for Treatment of Skin Infection - Jagdale, Swati C.; Kothekar, Payal V. (Recent Patents on Anti-Infective Drug Discovery, 2020)
Aim: To design controlled release topical delivery of mupirocin for the treatment of skin infection. Background: Mupirocin is an antibacterial drug. Mupirocin works to kill the bacteria, which include strains of Staphylococcus aureus and Streptococcus pyogenes. It is also used for the treatment of inflammation of a hair follicle. The half-life of mupirocin is only 20-40 min. It has very slight solubility in water. Patent literature had shown work on ointment, antibiotic composition, nasal and topical composition. Emulgel is a duel control release system for the topical delivery of hydrophobic drugs. Objective: The objective was to formulate emulgel with controlled delivery of mupirocin using Sepineo P 600. Methods: Soya oil, tween 80 and polyethylene glycol 400 (Oil:Surfactant:Cosurfactant) were used for emulsion formulation. Emulgel was optimized by 32 factorial design. Sepineo P 600 and hydroxy propyl methyl cellulose K4M were used as independent variables. Drug excipient compatibility analysis was carried out by FTIR, UV and DSC spectra. Emulgel was evaluated for its physical characterization, in vitro release, ex vivo release, antimicrobial and anti-inflammatory study. Results: DSC, UV and FTIR analysis confirmed drug excipient compatibility. FE SEM showed a size range between 228-255 nm. Zeta potential was found to be -25.1 mV, which showed good stability of the emulsion. Design expert software showed F2 as an optimized batch. Release studies indicated that the controlled release of drugs forms Sepineo P 600 gel due to its higher gelling capacity. Batch F2 showed comparable results with marketed formulation against Staphylococcus aureus. For batch F2, 40 μg/ml was the minimal inhibitory concentration. Conclusion: Antimicrobial and anti-inflammatory study proved successful development of stably controlled release mupirocin emulgel.
Keywords: emulgel